مخاطر الإنشاء الذّهني دراسة في رواية " ملكوت البسطاء " لخيري الذهبي - دواي رنا أمير (Latakia University Journal - Arts and Humanities Sciences Series, 2013)
يهدف هذا البحث إلى مقاربة قضيّة مخاطر الإنشاء الذّهني التي تُعنى بقراءة التجلّيات التي تبدو مرتبكةً إلى حدٍّ ما متمثّلةً باشتغال المبدع بتيماتٍ خاصّةٍ تستبق زمن الإبداع وحريّة مساراته، وهذا ما يتجلّى في أوّل أعمال الرّوائي السّوري خيري الذّهبي "ملكوت البسطاء" التي حاولتُ قدر الإمكان دراستها دراسةً وافيةً. This research aims to approach the issue of the risk of mental composition that focuses on scrutiny of the revelations that look ambiguous to some extent, as apparent in the creator’s obsession with special themes that precede the time of creativity and the freedom of its routes. This is quite obvious in the primary production of the Syrian novelist Kheiri al-Zahabi "Malakoot al-Busataa’" in which I have done my best to study it in a thorough artistic way.